2018
DOI: 10.1148/radiol.2018172597
|View full text |Cite|
|
Sign up to set email alerts
|

Ex Vivo Mercury Release from Dental Amalgam after 7.0-T and 1.5-T MRI

Abstract: Purpose To evaluate ex vivo mercury release from dental amalgam after 7.0-T and 1.5-T MRI. Materials and Methods The authors evaluated 60 caries-free molar or premolar teeth that had been extracted for clinical indications. Two-sided cavities were opened in each tooth and amalgam fillings applied. After 9 days, two groups of 20 randomly selected teeth were placed in 20 mL of artificial saliva immediately followed by 20 minutes of MRI exposure at 1.5 or 7.0 T. A control group of teeth was placed in artificial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
0
17
3
2
Order By: Relevance
“…Elemental Hg (metallic Hg 0 ), inorganic Hg salts and organic Hg compounds are three different chemical forms of Hg . Elemental Hg (Hg 0 ) can be derived from old clinical thermometers, thermostats, latex paint and dental amalgams . In the general population, dental amalgams represent the primary source of exposure to inorganic Hg .…”
Section: Occupational Exposure To Mercurymentioning
confidence: 99%
“…Elemental Hg (metallic Hg 0 ), inorganic Hg salts and organic Hg compounds are three different chemical forms of Hg . Elemental Hg (Hg 0 ) can be derived from old clinical thermometers, thermostats, latex paint and dental amalgams . In the general population, dental amalgams represent the primary source of exposure to inorganic Hg .…”
Section: Occupational Exposure To Mercurymentioning
confidence: 99%
“…Baş boyun bölgesini görüntülemek için kullanılan görüntüleme yöntemlerinin dental materyaller ile etkileşimi çalışılan bir konudur (14)(15)(16)(17). Bazı görüntüleme yöntemlerinin amalgam dolgulardan cıva salınımını harekete geçirdiği bildirilmiştir (14,18).…”
Section: İstatistiksel Yöntemunclassified
“…Diş hekimliği pratiğinde kesitsel ve 3 boyutlu görüntülemeye olanak sağlayan konik ışın demetli bilgisayarlı tomografiye manyetik rezonans görüntülemenin amalgam dolgular üzerine etkisini mikrosızıntı ve cıva salınımı konularında test ettik (16,18…”
Section: İstatistiksel Yöntemunclassified
“…Salivary analysis of mercury provides a relatively easy measure to compare mercury levels in children with ADHD and those without ADHD. [15][16][17][18] While few studies have successfully shown increased mercury levels in the blood, urine, and saliva of individuals with ADHD, 13,14,19 there has been no systematic attempt made to evaluate the age, demographic, or oral health factors that could influence the levels of mercury in the saliva of children with ADHD when compared to age-and gender-matched controls.…”
Section: Introductionmentioning
confidence: 99%